Individually and socially-based understandings in researching professional discourse - Arundale, Robert B. (Journal of Modern Languages, 2017)
Scholars both in the West and in Asia have repeatedly observed that much theorizing on discourse phenomena by Western scholars has privileged explanations in terms of humans as individual beings, rather than in terms of humans as social beings. Key examples in the study of professional discourse are theories explaining face and politeness, with theories of human communication, leadership, and management similarly focused. Face, as one particular example, is a concept drawn from Asian discourse regarding how persons relate to one another, but which in the hands of Western scholars has been re-conceptualized as an attribute of a singular individual, rather than as a social property of persons-in-relationship-to-other-persons. Scholars both in the West and in Asia employ these Western theories in research on professional discourse (Bargiella-Chiappini et al., 2007), there being at present no prominent explanation that privileges explanations in terms of humans as social beings, or more productively, in terms of humans as dialectically both individual beings and social beings. Employing an individually-based account at the expense of a socially-based account is consequential in examining discourse because the way in which a scholar conceptualizes a phenomenon constrains the questions he or she addresses in research, the explanations he or she creates, and the applications of his or her findings.